Corporate governance regulation, legal origin and small business access to credit: a cross-european comparison - Maresch, Daniela; Moro, Andrea; Fink, Matthias (Financial Management Association, 2016)
In this cross-European study, we investigate the impact of two specific corporate governance mechanisms (shareholder rights and regulations on related-party transactions) on firms’ decision to apply for credit and the banks’ lending decision. We argue that this impact is contingent upon the legal origin that shapes the regulatory institutional setting in which the corporate governance mechanisms are embedded. We perform a cross-European comparison based on 45,596 firm-level observations from 13 countries. Logit regression reveals that corporate governance does not directly influence the banks' lending decision or the firms' decision to apply for credit. Rather, the impact of corporate governance on firms’ credit access unfolds through regulatory institutional contexts that are shaped only by specific legal origins. Our findings help to explain why firms in different countries are financed so differently by highlighting the relevance of the embeddedness of corporate governance mechanisms in regulatory institutional settings. For research, our findings call for more multi- level work. For business practice, our findings imply that a well-designed governance regime regarding shareholder protection can foster firms’ access to bank finance, and thus innovation and economic growth. For legislators, we highlight the importance of ensuring a fit between corporate governance mechanisms and the specifics of the national regulatory environment.
Keywords: Corporate Governance; Credit Access; Legal Origin; Europe; Comparison